A BRIEF ANALYSIS OF KHUSRAV DEHLAVI'S PERSIAN WORK (Archive of Conferences, 2020)
Amir Khusrav created in all genres of Persian literature of his time. He is a philosopher-artist, who is rarely found in the field of rubai. The whole work of the poet is full of philosophical observations about the Truth, the universe, man, life, the earth, love, and this heritage has become a unique monument as a result of the correct use of the power of words in it. His great achievements in this field are also related to the poet's poetry. Although the theme of love, which is characteristic of the whole poetry in his rubai, is a stable factor, the field of social and philosophical observation is very wide. As a skilled artist who has mastered the art of speech, he amazes people with his ability to perform any subject.